Reviews of Environmental Contamination and Toxicology - Whitacre, David M.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
RECT 203 edited David M. Whitacre Forward Preface Bioavailability of Xenobiotics in the Soil Environment by Arata Katayama et al. Effects of Pesticides on Freshwater Diatoms by E. Pinelli et al The Toxic Effects of Formaldehyde on the Nervous System by Ahmet Songur et al. Dermal Toxicity and Environmental Contamination: Electron Transfer, Reactive Oxygen Species, Oxidative Stress, Cell Signaling and Protection by Antioxidants by Peter Kovacica and Ratnasamy Somanathan 5. Heavy Metals Alter the Potency of Medicinal Plants by Sekh Abdul Nasim and Bhupinder Dhir Index
Bioavailability of Xenobiotics in the Soil Environment -- Effects of Pesticides on Freshwater Diatoms -- The Toxic Effects of Formaldehyde on the Nervous System -- Dermal Toxicity and Environmental Contamination: Electron Transfer, Reactive Oxygen Species, Oxidative Stress, Cell Signaling, and Protection by Antioxidants -- Heavy Metals Alter the Potency of Medicinal Plants.
Keywords: Environmental sciences; Environmental management; Environmental toxicology; Waste disposal; Environment; Environmental Management; Ecotoxicology; Waste Management/Waste Technology